Recovery of a Fully Viable Chimeric Human Parainfluenza Virus (PIV) Type 3 in Which the Hemagglutinin-Neuraminidase and Fusion Glycoproteins Have Been Replaced by Those of PIV Type 1 - Tao, Tao (American Society for Microbiology, 1998)
The recent recovery of human parainfluenza virus type 3 (PIV3) from cDNA, together with the availability of a promising, highly characterized live attenuated PIV3 vaccine virus, suggested a novel strategy for the rapid development of comparable recombinant vaccine viruses for human PIV1 and PIV2. The strategy, illustrated here for PIV1, is to create chimeric viruses in which the two protective antigens, the hemagglutinin-neuraminidase (HN) and fusion (F) envelope glycoproteins, of an attenuated PIV3 variant are replaced by those of PIV1 or PIV2. As a first step, this has been achieved by using recombinant wild-type (wt) PIV3 as the recipient for PIV1 HN and F, engineered so that each PIV1 open reading frame is flanked by the existing PIV3 nontranslated regions and transcription signals. This yielded a viable chimeric recombinant virus, designated rPIV3-1, that encodes the PIV1 HN and F glycoproteins in the background of the wt PIV3 internal proteins. There were three noteworthy findings. First, in contrast to recently reported glycoprotein replacement chimeras of vesicular somatitis virus or measles virus, the PIV3-1 chimera replicates in LLC-MK2 cells and in the respiratory tract of hamsters as efficiently as its PIV1 and PIV3 parents. This is remarkable because the HN and F glycoproteins share only 43 and 47%, respectively, overall amino acid sequence identity between serotypes. In particular, the cytoplasmic tails share only 9 to 11% identity, suggesting that their presumed role in virion morphogenesis does not involve sequence-specific contacts. Second, rPIV3-1 was found to possess biological properties derived from each of its parent viruses. Specifically, it requires trypsin for efficient plaque formation in tissue culture, like its PIV1 parent but unlike PIV3. On the other hand, it causes an extensive cytopathic effect (CPE) in LLC-MK2 cultures which resembles that of its PIV3 parent but differs from that of its noncytopathic PIV1 parent. This latter finding indicates that the genetic basis for the CPE of PIV3 in tissue culture lies outside regions encoding the HN or F glycoprotein. Third, it should now be possible to rapidly develop a live attenuated PIV1 vaccine by the staged introduction of known, characterized attenuating mutations present in a live attenuated PIV3 vaccine candidate into the PIV3-1 cDNA followed by recovery of attenuated derivatives of rPIV3-1.